THE BIOLOGICAL CHARACTERISTICS OF CORALS IN THE WILD AND CULTURE CONDITIONS - Thuy, Nguyen Thi Thanh (Vietnam Journal of Marine Science and Technology, 2012)
Based on the reef building ability relying on symbiotic zooxanthellae, corals can be classified into reef building hermatypic corals and non reef building ahermatypic corals. Based on the presence or absence of outer skeleton, corals can be divided into stony corals and soft corals. For the purpose of feeding, the corals can be classified into large/long polyp stony (LPS) and small/short polyp stony (SPS) corals. All soft corals have eight tentacles on the polyps so called “Octocorallia”. Almost all the hermatypic corals are colonial, with individual polyps. The autotrophic mode of feeding is majority mode in the hermatypic corals with 50 - 95% of the energy budget from photosynthesis depending on species. However, the corals possess the ability of three hetrotrophic modes of feeding: predatory prey capture by the polyps; Sedimentary filter feeding using mucus nets and consume dissolved organic matter through cell membranes. In culture condition, the common food for corals is nauplii of Artemia salina. Besides, corals can consume processed seafood with suitable sizes. Most corals are hermaphroditic, some corals are gonochorism.Sexual and asexual reproduction is observed in corals. Competitive and defensive mechanisms of corals include rapid growth, aggressive structures, sweeper tentacles and toxic compounds. Suitable environmental parameters for corals in the wild and culture conditions: light intensity from 30 - 80% photosynthesis available ratio (PAR0), temperature 23 - 270C; pH 8 - 8.45; alkalinity 2.5 - 4meq/L (7 - 11dkH); salinity 35‰; concentrations of the mineral nutrition are similar to natural marine water (NH+4: 3.8µM/L; NO3--: 3.8µM/L; PO4--: 0.56µM/L); calcium 350 - 450ppm; strontium 8 - 10ppm; the presense of water flow providing oxygen and food transfer for corals, concurrently, sedimentation prevention and anti-fouling on surface of the corals.